Group Reputation, Anonymous Matching, and External Monitoring in a Model of Corruption - WANG, Huan (Institutional Knowledge at Singapore Management University, 2010)
We explore what group reputation is and model its formation and evolution. Based solely on group signals, we define a player’s group reputation as the belief that others have about the characteristics of the group the player belongs to. A model of group reputation of civil servants with anonymous matching and external monitoring is constructed to characterize the strategic behavior of potential bribers and civil servants, the corresponding levels of corruption, possible anti-corruption policies, and the effects of these policies. Our results indicate that as there are two types of corruption behavior of civil servants: accepting bribes and dereliction of duty, anti-corruption should work along both lines.